Strategy for Using Instagram as a Digital Marketing Communication Media to Increase MSME Product Sales - Clarissa Karin; Rizka Putri Abner (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Marketing communication helps MSME businesses to increase sales of their products or services by informing potential customers about the type of product they choose, how they buy it, the benefits they get, and the products and services they offer. Advances in marketing communication currently occur not only traditionally but also digitally through social media such as Instagram. Digital marketing communication that requires social media to reach the wider community and is expected to have an impact on increasing sales of MSME products, so this study aims to determine the strategy for using Instagram as a digital marketing communication medium to increase sales of MSME products. This type of research uses descriptive qualitative with a phenomenological approach that seeks to let reality reveal itself naturally through questions, the research subject tells all kinds of dimensions of his experience related to a phenomenon or event. Furthermore, obtaining objective data, it can be done through field research, by collecting data through observation and interviews, and documentation. Meanwhile, the respondents are MSME actors who use Instagram as a communication medium for the digital marketing of their products/services and are located in Cirebon. In addition, data collection uses documentation in the form of books or documents, journals, the internet, and other sources related to this research. While the data analysis technique in this study uses 3 stages, namely data reduction (data reduction), data presentation (data display), and conclusion drawing (verification). The results of the study explain that the use of the features available on Instagram is very helpful for MSME actors to improve their products. His services. For example, features on photo/video uploads, captions, likes, arroba, comments, hashtags, direct massage, live Instagram, location tags, and Instagram stories. From these features, MSME business players always try to maximize it to increase sales of their products/services. Even MSME business people feel the positive impact of increasing sales on the use of Instagram